Pengaruh Quality Of Work Life Dan Burnout Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Moderasi (Studi Pada Karyawan Warehouse PT Tirta Sukses Perkasa) - Pratiwi, Cantika Puspa; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Representatives with tall execution can play a noteworthy part in an organization. This ponder points to look at the impact of quality of work life and burnout on representative execution through inspiration as a directing variable at PT Tirta Sukses Perkasa. The test of this think about comprises of 113 distribution center representatives. The information collection procedure utilized in this inquire about could be a survey. The ponder utilizes the Basic Condition Modeling - Fractional Slightest Square (SEM-PLS) strategy with Smart-PLS form 4.0 computer program. The comes about of the think about demonstrate that quality of work life does not have a noteworthy impact on worker execution, burnout does not have a noteworthy impact on representative execution, inspiration does not direct the relationship between quality of work life and worker execution, and inspiration moderates the relationship between burnout and representative execution.   Keywords: Quality of work life, Burnout, Employee Performance, Motivation